Traditional Bamboo Products and their Market Sustainability in the Wake of Globalization - an Opportunity Cost Analysis - Anitha, V.; Muraleedharan, P. K.; Santheep, K. V. (Indian Forester, 2008)
The Traditional Bamboo Dependent (TBDs) community produce traditional bamboo products for their subsistence as well as for meeting the local seasonal demand. Bamboo based production activities of TBDs involve four stages, viz., collection of raw materials, processing, production and marketing. The raw material requirement of the bamboo dependents is mainly sourced from the private depots, home gardens and forest. Production is a highly time consuming laborious activity. A market analysis of the bamboo products highlights that the opportunity cost is greater than the earned benefit and the community is under-paid even during the peak period of sales. Plastic and rubber industry offer various substitutes to the bamboo products of TBDs and pose a threat to the existence of these environment-friendly products in the long run. The paper highlights that for ensuring the sustainable development of the sector, the apt strategy would be long-term market development, product-education, product diversification, introduction of modern technology and expansion of market.